VESTIBULAR NEURONITIS - Shahdevi Nandar Kurniawan; Afiyfah Kaysa Waafi (Journal of Pain, Headache and Vertigo, 2021)
Vestibular neuronitis is an acute vestibular syndrome due to inflammation of the vestibular nerve characterized by the typical symptoms of acute rotatory vertigo accompanied by nausea, vomiting, and symptoms of balance disorders. The incidence of vestibular neuronitis is about 3.5 per 100,000 people. The exact etiology of this vestibular neuronitis is unknown. However, based on existing evidence, vestibular neuronitis is associated with viral infections of the upper respiratory tract and herpes zoster infection. The clinical manifestations of vestibular neuronitis are persistent rotatory vertigo accompanied by oscillopsia, horizontal-rotatory peripheral vestibular spontaneous nystagmus on the healthy side, and a tendency to fall on the affected side. Diagnosis of vestibular neuronitis can be made by clinical diagnosis, through history, physical examination, and special examinations. Through these examinations, the differential diagnosis of vestibular neuronitis should be excluded, such as Meniere's disease, labyrinthitis, benign paroxysmal positional vertigo, and vertigo due to central lesions such as cerebellar infarction. Management of vestibular neuronitis is in the form of symptomatic therapy with vestibular suppressants, antivertigo, and redirect to relieve the symptoms that arise, then causative therapy can be done by administering corticosteroids, and in patients, physiotherapy can be done to improve vestibular function.